Recent developments on pse education and research in Malaysia - Hussain, Mohd Azlan; Manan, Z.A.; Aziz, N. (Computer Aided Chemical Engineering, 2012)
Process systems engineering (PSE) is a relatively young area in chemical engineering. The term PSE was used for the first time in the 1961 AICHE symposium series and became more established in Asia in 1982 after the first international symposium in Kyoto, Japan. The development of PSE education and research in Malaysia have taken shape within the last 15 years. PSE has recently evolved into a generic tool for the planning and management of policies as well as resource supply-chain that transcends the process domain. This paper presents the development of PSE education and research in Malaysia. Special highlights are given on the elements of innovation in PSE education and on various research works done by institutions in Malaysia including those that fits the big picture of systems planning and engineering.